Comparison of cell lineage development and regulation during early embryonic development in cattle and mice - WU Xiaotong; SHI Yan; LI Shuang; WANG Shaohua; ZHANG Kun (浙江大学学报. 农业与生命科学版, 2023)
Low reproductive efficiency of high-yielding dairy cows is a worldwide challenge, among which the high mortality rate of early embryos is one of the main reasons. Scientists have gained insightful knowledge into early embryonic development in mice while very little work has been performed in cattle. To better understand the early embryonic development in cattle, we compared early embryonic development in cattle and mice from the perspectives of embryo morphology, transcription factors and signaling pathways. It was found that after fertilization, degradation of maternal factors, zygotic genome activation, construction of cell polarity and asymmetric division occurred at different periods in the early embryos of cattle and mice. Eventually, embryos develop to blastocysts with three germ layers (trophectoderm, epiblast and primitive endoderm). Furthermore, multiple transcription factors and signaling pathways form complicated networks to regulate cell lineage differentiation during early embryonic development in cattle and mice. In summary, similar biological events occur one after another at the early embryonic development in cattle and mice, but the regulation of cell lineage differentiation is different, suggesting the limitations of using the early embryo of mouse as a research model. The study in this field plays a crucial role in improving reproductive efficiency of dairy cows and promoting the genetic improvement in cattle.